Krüppel-like factor 4 control of immune cell function - Das, Tapatee; Wang, Elaine; Xu, Yitian; Yang, Harrison; Liao, Xudong; Jain, Mukesh K. (Frontiers in Immunology, 2025)
Krüppel-like factor 4 (KLF4) belongs to a family of transcription factors that contain conserved zinc finger DNA binding domains, including specificity proteins (SPs) and Krüppel-like factors (KLFs). KLF4 plays a vital role in regulating cellular differentiation, proliferation and adaptation to a broad spectrum of internal and external cues. In the context of the immunity, KLF4 is appreciated as critical to both the innate and adaptive arms of the immune system. The current review article focuses on these aspects of KLF4 action as well as implications of this work for impacting human health.